Rise of Online Shopping in Shopee: Is Shopee Xpress Satisfying to Consumers? - Mock, Wan Yue; Meng, Xiaoyong; Azhar, Mohamad Affan Wajdi Bin Mohd; Hamzah, Mohamad Afiq bin; Tyagi, Ritika (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
As a tremendous expansion of online shopping on Shopee, Shopee Xpress Shipping Programme is launched to provide consumers with the most dependable pickup and delivery services. Nonetheless, Shopee Xpress encountered operational difficulties to meet Shopee's ever-increasing demand while ensuring consumer satisfaction. The objective of this research is to evaluate how satisfied consumers are with Shopee Xpress when they shop online on Shopee. In this research, four independent variables are studied, which are assurance, convenience, reliability, and price. A total of 150 respondents took part in an online survey via Google Forms. In conclusion, this research contributes to a deeper understanding of the consumer satisfaction of Shopee Xpress as an e-commerce service for online shopping on Shopee. Keywords: Consumer Satisfaction, E-commerce Service, Online Shopping, Shopee, Shopee Xpress